Glaucoma Origin, Diagnosis and Modern Clinical Diagnostic Methods - Shohboz, Muxtorov; Rahmiddinovna, Ochilova Shirin (American Journal of Bioscience and Clinical Integrity, 2025)
Glaucoma is a leading cause of irreversible blindness, often progressing unnoticed until significant vision loss occurs. This study investigates the origin, diagnosis, and modern clinical diagnostic methods of glaucoma, highlighting the challenges in early detection and treatment. Despite advances in ophthalmology, a knowledge gap remains in improving early diagnostic techniques to prevent optic nerve damage. This research employs a comprehensive review of existing literature and clinical practices, emphasizing the role of intraocular pressure (IOP) assessment, optic nerve evaluation, and modern imaging technologies such as tonometry, optical coherence tomography, and perimetry. The findings indicate that early diagnosis remains challenging due to the asymptomatic nature of primary open-angle glaucoma (POAG), which accounts for nearly 90% of cases. Furthermore, risk factors such as age, genetics, and metabolic disorders contribute significantly to disease onset. The results suggest that integrating multimodal diagnostic tools and improving awareness among healthcare professionals and patients can enhance early detection rates. The implications of this study reinforce the need for routine screening programs and technological advancements in ophthalmic diagnostics to reduce the global burden of glaucoma-related blindness.